The Influence of Value Orientations, Personal Beliefs, and Knowledge about Resource Extraction on Local Leaders' Positions on Shale Development1. (29th May 2015) - Crowe, Jessica; Ceresola, Ryan; Silva, Tony
Abstract: Unconventional shale oil and gas production plays a prominent role in boosting economic growth and stimulating wealth creation in many communities. However, because of potential social and environmental drawbacks, including a lack of affordable housing and groundwater contamination from drilling, unconventional shale development is highly contentious in many areas and has resulted in many community conflicts. Hydraulic fracturing, which is a specific technology utilized in unconventional shale development, has proved especially contentious because of concerns about its long‐term environmental consequences. Given the fast pace of shale development, coupled with the controversy that surrounds it, we seek to understand what factors affect a local government official's stance on shale development and hydraulic fracturing. To do this we draw from value‐belief‐norms theory while additionally examining knowledge and community‐level factors that can influence an official's position. In this study, we survey 308 local government officials across six shale plays in the United States to examine local officials' positions on shale development and hydraulic fracturing. We find that the more positively officials perceive the consequences of shale development, the less likely they are to support banning hydraulic fracturing. Additionally, we find that networks to other shale communities are positively associated with favoring a ban. Further, leaders with a bachelor's degree or higher are more likely to favor a ban than those with lower than a bachelor's degree.